Enhancing Sustainable Marine Tourism: The Crucial Role of Environmental Conservation Programs in West Nusa Tenggara - Islahuddin; Ali Muhtasom; Anwari Masatip; Herman Herman (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
Marine tourism in West Nusa Tenggara (NTB) presents significant economic opportunities but poses risks to environmental sustainability without proper conservation efforts. This research explores how environmental conservation can be integrated into sustainable marine tourism development strategies to ensure that tourism growth does not harm NTB's natural resources. The study adopts a quantitative approach, surveying 100 key stakeholders, including tourism professionals and local Government officials, to analyze the relationship between environmental conservation and sustainable tourism success. Using multiple linear regression, the research reveals that public awareness of environmental conservation significantly impacts tourism sustainability. In contrast, Government actions and conservation efforts are perceived as less effective. The findings emphasize that challenges in conservation can motivate improvement efforts, suggesting that stakeholder collaboration is crucial in addressing obstacles and enhancing marine tourism's long-term viability. This study provides a basis for developing policies promoting economic growth and environmental protection in NTB, demonstrating that sustainable tourism can yield substantial economic benefits while preserving natural ecosystems. These insights aim to guide future efforts to balance tourism development with environmental conservation, establishing NTB as a model for sustainable marine tourism.